Ultrafast carrier dynamics and THz conductivity in epitaxial-grown LT-GaAs on silicon for development of THz photoconductive antenna detectors - Afalla, Jessica (Animo Repository, 2021)
Carrier dynamics and photoconductivity in epitaxial-grown low-temperature GaAs on nominal and vicinal Si(1 0 0) substrates ('LT-GaAs/Si') were studied to predict their actual performance as THz photoconductive antenna (PCA) detectors. An optical-pump terahertz-probe technique was used to obtain the transmittance, carrier lifetime and photoconductivity of two LT-GaAs/Si samples, grown using different substrates and different growth protocols. The LT-GaAs grown on Si(1 0 0) substrate with a 4° tilt to 1 1 0 has better crystallinity, in agreement with other reports; while the LT-GaAs layer grown on nominal Si(1 0 0) substrate, though more structurally defective, has a much faster electron trapping time. Fabricated test PCAs with either dipole or bowtie geometries confirm the characterization results. The photoconductivity and carrier lifetime results manifest in the PCA performance, in responsivity, and in detection bandwidth. The prototypes' sensitivities, bandwidths and dynamic ranges show that with some growth optimization, LT-GaAs/Si can be tailored to create economical, broadband THz detectors. © 2019 IOP Publishing Ltd.